Enzyme-linked immunosorbent assay for aflatoxin B1 using a portable pH meter as the readout. Issue 30 (24th July 2018) - Chen, Juanjuan; Wang, Lixu; Zhao, Mengmeng; Huang, Da; Luo, Fang; Huang, Liying; Qiu, Bin; Guo, Longhua; Lin, Zhenyu; Chen, Guonan
Abstract : A simple and portable biosensor was developed for aflatoxin B1 determination using a portable pH meter as the readout. Abstract : The pH meter, one of the most common sensors for laboratory measurements, has the advantages of excellent sensitivity, low price, high reliability, and ease of use. In this study, the high sensitivity of the pH meter was coupled with the high selectivity of immunosorbent assay to develop a simple and portable biosensor for aflatoxin B1 (AFB1 ) determination. Urease was first labelled on the AFB1 antigen, in the presence of AFB1 ; the target competed with the urease-labeled AFB1 antigen to be captured by the antibody. Urease could catalyse the hydrolysis of urea into ammonia and induce the pH increase of the solution; the change could easily be detected using a handheld pH meter or pH-sensitive dye. Under optimized conditions, the pH value enhancement had a linear relationship with the logarithm of the concentration of AFB1 in the range of 0.62 to 23.42 ng mL −1 . The proposed biosensor has been applied to detect AFB1 in real samples with satisfactory results.